Experimental investigation on transient characteristics of a dual compensation chamber loop heat pipe subjected to acceleration forces. (5th February 2018) - Xie, Yongqi; Zhou, Yang; Wen, Dongsheng; Wu, Hongwei; Haritos, George; Zhang, Hongxing
Highlights: The DCCLHP transient performance is studied experimentally in acceleration field. Acceleration effect significantly impacts the startup behavior at small heat load. Acceleration effect can change the operating mode and relevant heat load range. Temperature oscillation and reverse flow phenomena are observed in the experiment. Abstract: In this article, an experimental study has been conducted to provide better understanding of the transient characteristics of a dual compensation chamber loop heat pipe (DCCLHP) subjected to the acceleration force. A new acceleration test rig was set up to provide the acceleration up to 11 g with three different directions. The heat load on the evaporator ranging from 25 W to 300 W was applied with the acceleration force simultaneously. Experimental results indicated that the DCCLHP could start up at a small heat load of 25 W and the startup behavior was different under acceleration direction conditions because of the vapor-liquid distribution change in the evaporator and compensation chambers (CCs). Under the current operating conditions, the effect of acceleration force was significant to the operating performance at small heat loads whereas was weak at large heat loads. Experimental results also clearly showed that both acceleration magnitude and direction can alter the operating mode. What's more, it was found that temperature oscillation, reverse flow and evaporation in the evaporator core phenomena occurred under acceleration conditions.